Comparison of Sutureless Versus Suture Partial Nephrectomy for Clinical T1 Renal Cell Carcinoma: A Meta-Analysis of Retrospective Studies - Zhang, Wenjun; Che, Bangwei; Xu, Shenghan; Mu, Yi; He, Jun; Tang, Kaifa (Frontiers in Oncology, 2021)
Background: Partial nephrectomy (PN) is the recommended treatment for T1 renal cell carcinoma (RCC). Compared with suture PN, sutureless PN reduces the difficulty and time of operation, but the safety and feasibility have been controversial. This meta-analysis was conducted to compare the function and perioperative outcomes of suture and sutureless PN for T1 RCC. Methods: Performed systematic literature review up to April 2021 using multiple databases to identify eligible comparative studies. According to the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) criteria conducted Identification and selection of the studies. Performed meta-analysis for studies comparing suture to sutureless PN for both T1a and T1b RCC. In addition, subgroup analysis was performed on operation time, warm ischemia time, estimated blood loss, and postoperative complications. Sensitivity analysis was used in analysis with high heterogeneity (operation time and estimated blood loss). Results: Eight retrospective Studies were included with a total of 1,156 patients, of 1,156 patients, of whom 499 received sutureless PN and 707 received suture PN. The results showed that sutureless PN had shorter operative time (I2=0%, P<0.001), warm ischemia time (I2=97.5%, P<0.001), and lower clamping rate (I2=85.8%, P=0.003), but estimated blood loss (I2=76.6%, P=0.064) had no difference. In the comparison of perioperative outcomes, there was no significant difference in postoperative complications (I2=0%, P=0.999), positive surgical margins (I2=0%, P=0.356), postoperative eGFR (I2=0%, P=0.656), and tumor recurrence (I2=0%, P=0.531). Conclusions: T1a RCC with low R.E.N.A.L score, sutureless PN is a feasible choice, whereas should not be overestimated in T1b RCC.